2019
DOI: 10.7759/cureus.4465
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Bone Hydatidosis: A Dangerous Crippling Disease

Abstract: Hydatid disease is one of the most complicated and devastating conditions caused by Echinococcus granulosus . This globally distributed disease continues to be an important public health concern in many low- and middle-income countries. The liver and the lungs are the most frequently involved sites, but virtually any organ system can be affected. Osseous hydatidosis is relatively less common, but it is extremely debilitating and difficult to manage due to frequent recurrences. Patients o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(31 citation statements)
references
References 17 publications
(30 reference statements)
1
30
0
Order By: Relevance
“…The larvae released from the eggs penetrate the intestinal wall and migrate to various organs. In addition to having a clear history of pastoral contact, a relatively higher prevalence has been noted in the rural populations that is mainly attributable to the slaughtering of animals in these areas [1]. In this study, we found that three patients were shepherds with a definite epidemiological history, and nine patients were all farmers.…”
Section: Clinical Features and Epidemicsupporting
confidence: 47%
See 2 more Smart Citations
“…The larvae released from the eggs penetrate the intestinal wall and migrate to various organs. In addition to having a clear history of pastoral contact, a relatively higher prevalence has been noted in the rural populations that is mainly attributable to the slaughtering of animals in these areas [1]. In this study, we found that three patients were shepherds with a definite epidemiological history, and nine patients were all farmers.…”
Section: Clinical Features and Epidemicsupporting
confidence: 47%
“…Specific antibody examinations are used for diagnosis including the following: the Casoni test, indirect hemagglutination (IHA), counterimmunoelectrophoresis (CIE), enzyme-linked immunosorbent assay (ELISA), and gold-labelled antibody [ 4 ]. Routine blood tests may reveal nonspecific inflammatory trends such as eosinophilia, deranged liver function tests, and raised CRP and erythrocyte sedimentation rate (ESR) [ 1 ]. In this group, only 5 cases underwent enzyme-linked immunosorbent assay (anti-EgcF antibody, anti-EgP antibody, anti-EgB antibody, and anti-Em2 antibody were all positive).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we used the surgical method and tried to eradicate the parasite using albendazole. Oral chemotherapy with Albendazole was continued for four weeks to prevent the possibility of cyst regrowth from surgical debris in the surrounding soft tissues (16). In our case, according to the patient's history, both a new infection J o u r n a l P r e -p r o o f (because of close contact with animals) and a secondary infection due to a previous cyst were possible.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 84%
“…Human hydatid disease is caused by the tapeworm Echinococcus granulosus , causing cystic hydatid disease. 1 5 Humans act as intermediate hosts and are infected by faecal oral spread, particularly when in contact with dogs infected with echinococcosis , who then shed the tapeworm eggs in their faeces. 3 , 5 7 Hydatid disease commonly affects the liver (75%), followed by the lungs (15%).…”
Section: Introductionmentioning
confidence: 99%